Analisis Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi di Sumtera Utara - Rahmat Esa Putra; Yeniwati Yeniwati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
The purpose of this study was to find out and analyze: (1) To what extent does thedegree of fiscal decentralization influence economic growth in North Sumatra,(2) To what extent does transfer dependency influence economic growth in NorthSumatra, (3) To what extent does the capital expenditure ratio influenceeconomic growth in North Sumatra, (4) How far is the degree of fiscaldecentralization, transfer dependence, and the ratio of capital expenditure toeconomic growth in North Sumatra. The data used is panel secondary data for33 regencies/cities in North Sumatra from 2014-2019, data obtained frominstitutions related to the research variables which are grouped into two parts,namely the dependent variable which in this study uses economic growth and theindependent variables which consist of degree of fiscal decentralization, transferdependency, and capital expenditure ratio. This study uses panel data regressionanalysis using the fixed effect model (FEM). The results of this study indicate thatsimultaneously, fiscal decentralization has a significant effect on economicgrowth in North Sumatra. while partially (1) The degree of fiscal decentralizationhas a negative and significant effect on economic growth (2) transfer dependencehas a positive and insignificant effect on economic growth (3) the ratio of capitalexpenditure has a positive and insignificant effect on economic growth in NorthSumatra.